All‐Inorganic Colloidal Perovskite Quantum Dots: A New Class of Lasing Materials with Favorable Characteristics. (8th October 2015) - Wang, Yue; Li, Xiaoming; Song, Jizhong; Xiao, Lian; Zeng, Haibo; Sun, Handong
Abstract : All‐inorganic colloidal cesium lead halide perovskite quantum dots (CsPbX3, X = Cl, Br, I) are revealed to be a new class of favorable optical‐gain materials, which show combined merits of both colloidal quantum dots and halide perovskites. Low‐threshold and ultrastable stimulated emission is demonstrated under atmospheric conditions with wavelength tunability across the whole visible spectrum via either size or composition control.